2020
DOI: 10.1101/2020.12.16.20248180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of anti-SARS-CoV-2 IgG antibodies, risk factors for infection and associated symptoms in Geneva, Switzerland: a population-based study

Abstract: BackgroundPopulation-based serological surveys provide a means for assessing the immunologic landscape of a community, without the biases related to health-seeking behaviors and testing practices typically associated with rt-PCR testing. This study assesses SARS-CoV-2 seroprevalence over the first epidemic wave in Canton Geneva, Switzerland, as well as biological and socio-economic risk factors for infection and symptoms associated with IgG seropositivity.Methods and findingsBetween April 6 and June 30, 2020, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
43
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 29 publications
11
43
2
1
Order By: Relevance
“…In this large sample of workers from 16 sectors who were mobilized during the spring 2020 Swiss lockdown, we observed that the proportion of workers having developed anti-SARS-CoV-2 antibodies after the first COVID-19 wave varied widely across sectors, across facilities within sectors and across occupations within sectors. With few important exceptions, our findings do not show a pattern of increased risk of SARS-CoV-2 infection among sectors and occupations of workers who were mobilized during the lockdown, the overall seropositivity rate of this sample being only slightly higher than that of the general working-age population during the spring 2020 21 . Yet, there was considerable variability across sectors and occupations.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In this large sample of workers from 16 sectors who were mobilized during the spring 2020 Swiss lockdown, we observed that the proportion of workers having developed anti-SARS-CoV-2 antibodies after the first COVID-19 wave varied widely across sectors, across facilities within sectors and across occupations within sectors. With few important exceptions, our findings do not show a pattern of increased risk of SARS-CoV-2 infection among sectors and occupations of workers who were mobilized during the lockdown, the overall seropositivity rate of this sample being only slightly higher than that of the general working-age population during the spring 2020 21 . Yet, there was considerable variability across sectors and occupations.…”
Section: Discussioncontrasting
confidence: 85%
“…Overall, 9.8% of individuals (1026/10513) tested positive for SARS-CoV-2 anti-S1 IgG antibodies (Table 1), roughly the same seropositivity rate (7.9% [95% CrI: 6.8-8.9]) as the general working-age population of Geneva over a similar time period 21 . Older participants (≥50 years) had a lower risk of being seropositive (RR: 0.70; 95% CrI: 0.56-0.83) compared with 18-34year-old participants.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Values higher than 1 suggest greater under-reporting of infections (due to both mild or asymptomatic infections, care-seeking behaviours, and testing practices). 27 USA, California, Marin (Appa et al 2020) 28 USA, California, Orange (Bruckner et al 2021) 29 USA, Connecticut (Mahajan et al 2020) 30 USA, Georgia, DeKalb and Fulton (Biggs et al 2020) 31 USA, Idaho, Blaine (McLaughlin et al 2020) 32 USA, Utah, four counties (Samore et al 2020) 33 Denmark, Faroe Islands (Petersen et al 2020) 34 Germany, Kreis Heinsberg, Gangelt (Streeck et al 2020) 35 Luxembourg (Snoeck et al 2020) 36 Netherlands (Vos et al 2020) 37 Russia, Saint Petersburg (Barchuk et al 2020) 38 Spain (Pollán et al 2020) 39 Switzerland, Geneva (Richard et al 2020) 40 Switzerland, Geneva (Stringhini et al 2020) 41 UK, England (Office of National Statistics 2020) 42 UK, England (Ward et al 2020) 43 UK, Jersey (Government of Jersey 2020) 44 India (Murhekar et al 2020 ) 45 India (Murhekar et al 2021) 46 India, Delhi (Sharma et al 2020) 47 India, Mumbai (Malani et might lead to mis-specification of assay performance. 53 Notably, although WHO has established a generic population-based serological study protocol, standardised guidelines and procedures for laboratory testing are scarce, which might contribute towards such heterogeneity in performance and reporting of results.…”
Section: Discussionmentioning
confidence: 99%
“…We identified one population study conducted in Hungary reporting on seroprevalence and smoking status (Merkely et al, 2020); however, the response rate was only 58.8% and the current smoking rate was 10 percentage points below national prevalence estimates, which raises some doubt about representativeness of the final sample. Similarly, two further representative population surveys (Carrat et al, 2020;Richard et al, 2020)…”
Section: Symptomatic Covid-19mentioning
confidence: 99%